Novel heavy metal resistance gene clusters are present in the genome of Cupriavidus neocaledonicus STM 6070, a new species of Mimosa pudica microsymbiont isolated from heavy-metal-rich mining site soil - Klonowska, Agnieszka; Moulin, Lionel; Ardley, Julie Kaye; Braun, Florence; Gollagher, Margaret Mary; Zandberg, Jaco Daniel; Marinova, Dora; Huntemann, Marcel; Reddy, T.B.K.; Varghese, Neha Jacob; Woyke, Tanja; Ivanova, Natalia; et al. (2020)
Background: Cupriavidus strain STM 6070 was isolated from nickel-rich soil collected near Koniambo massif, New Caledonia, using the invasive legume trap host Mimosa pudica. STM 6070 is a heavy metal-tolerant strain that is highly effective at fixing nitrogen with M. pudica. Here we have provided an updated taxonomy for STM 6070 and described salient features of the annotated genome, focusing on heavy metal resistance (HMR) loci and heavy metal efflux (HME) systems. Results: The 6,771,773 bp high-quality-draft genome consists of 107 scaffolds containing 6118 protein-coding genes. ANI values show that STM 6070 is a new species of Cupriavidus. The STM 6070 symbiotic region was syntenic with that of the M. pudica-nodulating Cupriavidus taiwanensis LMG 19424T . In contrast to the nickel and zinc sensitivity of C. taiwanensis strains, STM 6070 grew at high Ni2+ and Zn2+ concentrations. The STM 6070 genome contains 55 genes, located in 12 clusters, that encode HMR structural proteins belonging to the RND, MFS, CHR, ARC3, CDF and P-ATPase protein superfamilies. These HMR molecular determinants are putatively involved in arsenic (ars), chromium (chr), cobalt-zinc-cadmium (czc), copper (cop, cup), nickel (nie and nre), and silver and/or copper (sil) resistance. Seven of these HMR clusters were common to symbiotic and non-symbiotic Cupriavidus species, while four clusters were specific to STM 6070, with three of these being associated with insertion sequences. Within the specific STM 6070 HMR clusters, three novel HME-RND systems (nieIC cep nieBA, czcC2B2A2, and hmxB zneAC zneR hmxS) were identified, which constitute new candidate genes for nickel and zinc resistance.